Rethinking cities in a Post-COVID-19 world. - (:unkn) unknown (My University, 2020)
Aditi Ratho and Preeti Lourdes John: Editors’ Note (S. 6 ff.); Sheetal Ranganathan: Healthcare Delivery Must Embrace the Digital Space (S. 12 ff.); Oommen C Kurian: India’s Urban Healthcare System Must Adapt to the New Normal (S. 19 ff.); Elizabeth Hessek and Ashali Bhandari: Reimagining Urban Spaces for Community Connections and Climate Resiliency (S. 28 ff.); Tanushree Chandra: Building Blocks of a Post-COVID-19 Green City (S. 37 ff.); Amruta Ponkshe: Transportation Must Transform in the Post-Pandemic Era (S. 44 ff.); Saloni Atal: Women and the City: Embracing Gender-Sensitive Policies (S. 52 ff.); Aditi Ratho: Protecting the Future of Urban Workers in a Post-Pandemic Automated World (S. 60 ff.); Ramanath Jha: Providing Urban Poor with Livelihoods is Crucial Post COVID-19 (S. 67 ff.); Sangeet Jain: Reimagining the Workspaces of the Future (S. 74 ff.); Soumya Bhowmick: The Rise of Cities: Economic Drivers in the Post-Pandemic World (S. 81 ff.); Renita D’Souza: From Slums to Skyscrapers: Redesigning Urban Habitat Policies (S. 88 ff.); Manvita Barad, Kaninik Baradi: Inclusivity in Knowledge Cities in the Post-COVID-19 World (S. 96 ff.)
Keywords: Virus; Krisensituation; Gesundheitssystem; Stadtentwicklung; Stadtbegrünung; Inklusion; Nachhaltige Stadtentwicklung; Stadtwachstum; Slum; Transformation; Zukunftsentwicklung; Gesunde Stadt